Application of simulated presence therapy for hospitalized patients with dementia (模拟存在疗法在住院痴呆患者中的应用效果研究) - ZHANG Mengmeng (张萌萌); WANG Yan (王艳) (中西医结合护理)
Objective To investigate the effect of simulated presence therapy for hospitalized patients with dementia. Methods Totally 58 dementia patients were randomly divided into control group (n=26) and intervention group (n=25 ). The control group was given routine care, and the intervention group was given simulated presence therapy in addition to the routine care. The agitation level, cognitive function and anxiety state of dementia patients in the two groups were compared after two weeks of intervention. Results The Cohen-Mansfield Agitation Inventory (CMAI) score was decreased in two groups after the intervention, and was lower in the intervention group than that in the control group (P＜0. 05). There was no significant difference in the mini-mental status examination (MMSE) score between two groups before and after the intervention (P＞0. 05). The anxiety level of the intervention group was significantly lower than that of the control group after intervention(P＜0. 05). Conclusion Simulated presence therapy is potentially effective to reduce the agitation behavior and relieve the anxiety state of hospitalized patients with dementia. (目的 探究模拟存在疗法在住院痴呆患者中的应用效果。方法 51例痴呆患者随机将其分为对照组26例和干预组25例。对照组给予常规住院护理, 干预组在对照组基础上给予模拟存在疗法干预, 比较2组干预前后的激越水平、认知功能和焦虑状态。结果 干预后2组激越量表(CMAI)评分均降低, 干预组评分低于对照组, 差异有统计学意义(P＜0. 05)。干预前后, 2组简易精神状态检查表(MMSE)评分比较, 差异无统计学意义(P＞0. 05)。干预后, 干预组患者的焦虑水平显著低于对照组, 差异有统计学意义(P＜0. 05)。结论 模拟存在疗法能显著减少患者激越行为, 改善焦虑状态。)